Multi-Stressor Analysis of Climate Vulnerability in Indonesia: A Study on Environmental Policy Ethics and Maladaptation Risk - Alya Zahra Nabila (CV. Era Digital Nusantara, 2025)
Abstract: This article aims to explore climate change multi-stressors through the development of environmental policies in Indonesia. Over time, this tropical country has been increasingly exposed to global warming and climate change phenomena that generate significant national vulnerabilities. In addressing these challenges, policy attention has predominantly focused on climatic factors. However, vulnerability is not solely a climatic issue; rather, it reflects collective systemic incapacity, which is further exacerbated by extreme weather events. Vulnerability constitutes a core concept in environmental social sciences, yet existing discussions often remain climate-centric, with limited engagement with other contributing dimensions that intensify vulnerability. Purpose: This article seeks to analyze climate vulnerability multi-stressors in Indonesia, including an examination of environmental policy ethics and the risks of maladaptation. It aims to provide a foundational reference and contribute to broader knowledge and understanding of Indonesia’s vulnerability context for future research and policy applications. Design/Methodology/Approach: This study employs a secondary research methodology, drawing upon the analysis and synthesis of existing sources, particularly qualitative data related to environmental policies, climate vulnerability cases in Indonesia, and the implementation of relevant policies in addressing these challenges. Findings: Climate vulnerability in Indonesia remains relatively high. Efforts to address multiple stressors, particularly through policy formulation and implementation, continue to face significant obstacles and institutional stalling. Comprehensive and carefully designed planning is therefore essential to minimize maladaptation risks and to foster ethically grounded climate resilience. Originality/value: This study contributes to the field of environmental policy by addressing research gaps in existing literature concerning climate vulnerability in Indonesia, particularly about the role of multi-stressors and maladaptation risks in shaping vulnerability outcomes.